Predictors of Dysmenorrhea and Its Impact on Quality of Life among Tribal Adolescent Girls in India-A Cross Sectional Study - Udayar, Sharvanan E; Jeeragyal, Devika P; Kruthika, K (Unnes Journal of Public Health, 2022)
Dysmenorrhoea is the most common problem encountered by most of the adolescent girls .The study was conducted to find out the prevalence of dysmenorrhea, its risk factors and its impact on quality of life among these girls residing in tribal welfare hostels. A cross sectional study was conducted among 582 adolescent girls aged 10-19years residing in tribal welfare hostels in southern India after obtaining informed consent. Multinominal regression analysis was done to determine the factors associated with dysmenorrhea. The prevalence of dysmenorrhea was high with 58.4% and 48.8% participants reported to have physical premenstrual symptoms.There was significant association between those experiencing moderate to severe pain intensity and the dysmenorrhea (p<0.000). Association between factors like prolonged menstrual duration [AOR,3.40(95%CI,1.49-7.81)],those who were having moderate[AOR,5.78(95% CI,1.96-17.02)] to severe menstrual bleeding [AOR, 5.14 (95% CI, 1.78-14.08)],positive family history [AOR, 3.57 (95%CI,2.30-5.54)]and also with respect to somatic symptoms [AOR,2.03 (95%CI, 1.33-3.08] were statistically significant.44.7% of them ignored the pain during menstruation,followed by bed rest (33.5%),self medication(16.5%),hot application (4.1%). Strengthening of school health education programmes,incorporation of reproductive health issues in school curriculum will improve the barriers like knowledge on regarding menstrual cycle and treatment seeking behaviour among these vulnerable population.